2016
DOI: 10.1021/acssuschemeng.6b01149
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Gold Nanoparticles in Aqueous Solution by Microwave Assisted Flow Chemistry

Abstract: The development of energy efficient, reproducible and high throughput approaches to gold nanoparticles (Au-NPs) synthesis have gained increasing attention over the past decades due to their application in biomedicine, sensor and catalysis. In this work, single mode microwave irradiation is for the first time combined with microflow chemistry to fabricate Au-NPs continuously and reproducibly with controllable size in an aqueous solution. The major experimental parameters including microwave power, citrate-to-go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 51 publications
(176 reference statements)
0
62
0
Order By: Relevance
“…A continuous-flow reactor system has been proposed by many researchers. For example, Bayazit and coworkers [39] reported that the development of energy efficient, reproducible, and high throughput approaches to synthesize gold nanoparticles (Au-NPs) has gained increasing attention over the past decades owing to applications in biomedicine, sensors, and catalysis ( Figure 20). In their study, a single-mode microwave irradiation apparatus was combined for the first time with micro-flow chemistry to fabricate Au-NPs continuously and reproducibly with controllable size in an aqueous solution.…”
Section: Nanoparticle Synthesesmentioning
confidence: 99%
“…A continuous-flow reactor system has been proposed by many researchers. For example, Bayazit and coworkers [39] reported that the development of energy efficient, reproducible, and high throughput approaches to synthesize gold nanoparticles (Au-NPs) has gained increasing attention over the past decades owing to applications in biomedicine, sensors, and catalysis ( Figure 20). In their study, a single-mode microwave irradiation apparatus was combined for the first time with micro-flow chemistry to fabricate Au-NPs continuously and reproducibly with controllable size in an aqueous solution.…”
Section: Nanoparticle Synthesesmentioning
confidence: 99%
“…Variations of reaction conditions such as concentration, temperature and reaction time are likely to have a significant effect on both nucleation and particle growth, and a better control over these variables may improve the monodispersity, particle size and its distribution, shape and morphology, crystallinity and purity of the nanoparticles manufactured. [62,63] MI is believed to have more homogeneous heating throughout the solution, resulting in more accurate control on nucleation stage. The extra molecular level mixing force generated by microwave is further expected to help mass and energy transfer dramatically, achieving homogeneity throughout the bulk solution.…”
Section: Motivation Of Microwave Promoted Flow Systemsmentioning
confidence: 99%
“…The extra molecular level mixing force generated by microwave is further expected to help mass and energy transfer dramatically, achieving homogeneity throughout the bulk solution. [14,[62][63][64] However, there are some concerns about the use of MI in the large reactors involving microwave penetration depth, requiring strong microwave intensity, long irradiation time and high-pressure resistant reactors. In principle, a capillary reactor (< 1 mm diameter) promoted by MI can make use of all advantages of MI but exclude the drawbacks listed for large reactors.…”
Section: Motivation Of Microwave Promoted Flow Systemsmentioning
confidence: 99%
See 2 more Smart Citations